2022
DOI: 10.1073/pnas.2119463119
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomas assemble a filamentous CXCL12–keratin-19 coating that suppresses T cell–mediated immune attack

Abstract: Cancer immunotherapy frequently fails because most carcinomas have few T cells, suggesting that cancers can suppress T cell infiltration. Here, we show that cancer cells of human pancreatic ductal adenocarcinoma (PDA), colorectal cancer, and breast cancer are coated with transglutaminase-2 (TGM2)–dependent covalent CXCL12–keratin-19 (KRT19) heterodimers that are organized as filamentous networks. Since a dimeric form of CXCL12 suppresses the motility of human T cells, we determined whether this polymeric CXCL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…We recently reported that a CXCL12/KRT19-coat on mouse pancreatic ductal adenocarcinoma (PDA) cells impairs the accumulation of T cells in nests of cancer cells. CRISPR/Cas9-editing of the Krt19 gene in mouse PDA cells abolishes formation of the CXCL12/KRT19-coat and allows T cell infiltration in tumors formed with these edited cancer cells (Wang et al, 2022). This circumstance, enabled us to examine the effect of the presence of activated T cells in the tumor microenvironment (TME) on CAFs without perturbing other components of the TME that could alter the CAF phenotype, such as TGFβ (Mariathasan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that a CXCL12/KRT19-coat on mouse pancreatic ductal adenocarcinoma (PDA) cells impairs the accumulation of T cells in nests of cancer cells. CRISPR/Cas9-editing of the Krt19 gene in mouse PDA cells abolishes formation of the CXCL12/KRT19-coat and allows T cell infiltration in tumors formed with these edited cancer cells (Wang et al, 2022). This circumstance, enabled us to examine the effect of the presence of activated T cells in the tumor microenvironment (TME) on CAFs without perturbing other components of the TME that could alter the CAF phenotype, such as TGFβ (Mariathasan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Orthotopic tumors formed with mouse PDA cells differing only in their expression of Krt19 , which is required for assembly of the CXCL12/KRT19-coat, had contrasting TMEs that are immune-quiescent and immune-activated (Wang et al, 2022). We use this model to demonstrate two immunological principles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations